DETERMINATION OF NUCLEAR POWER PLANT SITE IN WEST BANGKA BASED ON ROCK MASS RATING AND GEOLOGICAL STRENGTH INDEX - Irvani Irvani; Wahyu Wilopo; Dwikorita Karnawati (Journal of Applied Geology, 2015)
Indonesian government through the NationalAtomic Energy Agency has planned to build anuclear power plant. One of the proposed sitesis in West Bangka Regency, Bangka BelitungArchipelago Province. The engineering geologyof this area is, however, not fully understood andrequires further investigations. Engineering geology investigations were carried out by assessing therock mass quality and bearing capacity based onfield observation and drilling data. The assessmentwas conducted using Rock Mass Rating (RMR)and Geological Strength Index (GSI) classifications.The rock masses in the study area were dividedinto four units, namely units of sandstone, granite,mudstone and pebbly sandstone. The RMR andGSI values in the study area were influenced by theparameters of discontinuity space density, the slopeof discontinuity orientation, grade of weatheringand groundwater conditions. The assessment showsthat the granite unit had the best quality which wasshown by a 53 average RMR value and 66 GSIvalue. Based on the average RMR value, the graniteunit was estimated to have cohesion value between0.2 and 0.3 MPa, friction angle between 25° and35°, and allowable bearing pressure between 280and 135 T/m2. Based on the GSI value, the graniteunit was estimated to have uniaxial compressivestrength value between 1.0465 and 183.8 MPa, ten-sile strength between (-0.0122) and (-5.2625) MPa,rock mass strength values between 24.5244 and220.351 MPa, and modulus of deformation withina range of 1.73 - 86.68 GPa. The Granite Unit wasconsidered to be the most appropriate location forthe nuclear power plants.